Analysis of human immune responses in quasi-experimental settings: tutorial in biostatistics. - Sarkar, Rajiv.; Ajjampur, Sitara S.; Ward, Honorine D.; Kang, Gagandeep.; Naumova, Elena N. (2016)
Background: Human immunology is a growing field of research in which experimental, clinical, and analytical methods of many life science disciplines are utilized. Classic epidemiological study designs, including observational longitudinal birth cohort studies, offer strong potential for gaining new knowledge and insights into immune response to pathogens in humans. However, rigorous discussion of methodological issues related to designs and statistical analysis that are appropriate for longitudinal studies is lacking.; Keywords: confidence interval, immune response measure, ELISA (Enzyme Linked Immune Sorbent Assay) units, polymerase chain reaction-restriction fragment length polymorphism, generalized linear model, generalized additive model, Student's t-test.; Springer Open.